Epidemiology of Viral Hepatitis from 2007 to 2016 in Karbala Governorate, Iraq - Merzah, Mohammed A. (J Res Health Sci, 2019)
Background: An escalation, as three times more, had been recognized in cases of hepatitis A (HAV) from 2009 to 2014 among Iraqi people. Regarding hepatitis B and C, Iraq is considered as a low endemic country comparing to neighbors. Study design: A retrospective cohort study. Methods: Data incorporated from 2007 to 2016 were collected through a federal survey conducted by the Health Directorate of Karbala, who administrates all hospitals (three public hospitals and five private hospitals) and 40 health centers in Karbala City, Iraq. The four types of hepatitis and demographic information of all cases were included. Results: A vivid shifting in the prevalence of HAV showed a decreasing pattern, that is, from 632 cases (PR=61) in 2007 to 314 cases (PR=33) in 2008. In 2012, its prevalence was twice greater (695 cases, PR=63.2). The PR of HBV also changed from 52 cases (PR=5.8) in 2007 to 26 cases (PR=2.8) in 2008. Regarding HCV, a decreasing pattern with 13 cases (PR=1.4) in 2007 and 12 cases (PR=1.2) in 2009 was seen. This number increased to 60 cases (PR=3.9) in 2016. For HEV, more cases were reported (47 cases, PR=4.7) in 2010. Conclusion: The four types of hepatitis have been highly prevalent since 2010. The high number of migrants to Karbala Governorate and unavailability of immunization might be reasons behind the high prevalence of the four-types of hepatitis.